The Establishment of Acoustical Privacy in Female Islamic Student Housing - I. Hasan, Muhammad; M.R. Aminuddin, Asrul; H.B. Mohidin, Hazrina; U. Pramesti, Previari (MAJ - Malaysia Architectural Journal, 2023)
The purpose of this paper is to investigate the establishment of acoustical privacy among residents of Islamic student housing for women in Semarang, Indonesia. In Islamic architecture, privacy is a prominent feature that must be incorporated into all structures, including student accommodation at an Islamic university. In Islamic architecture, acoustical privacy is substantially less investigated than visual privacy. Consequently, acoustical privacy is a significant issue that arises in the study of Islamic housing architecture. The theoretical sampling for the specific topic of acoustical privacy is developed utilising constructivism-grounded theory. Atlas.ti is utilised to assist researchers with coding, memo writing, and focused coding towards theoretical saturation in order to analyse interview data. Physical and non-physical aspects of establishing acoustical privacy among students are an intriguing discovery. Establishment consisting of walls, furniture, and personal belongings. While non-physical norms are unexpectedly revealed and unspoken among roommates. This study offers a fresh perspective on acoustical privacy in Islamic architecture, particularly in co-living communities.